Comparison of defect in conventional and IBS on residential building / Nurul Aziyani Zahari - Zahari, Nurul Aziyani (Faculty of Architecture, Planning and Surveying, 2013)
Housing is one of the main basic needs in life to achieve a standard of living that is perfect and comfortable. The main goal of the National Housing Policy is to ensure that every citizen of Malaysia, especially for low-income earners who have a desire to own their own homes have the opportunity to do so (Ministry of Housing and Local Government, 2007). This is because the house is a basic social need to achieve social development. However to own a home is not easy because it requires a large capital. It depends on the degree of home buyer affordability in which some household expenses should be used to have a house (Rosadah and Khadijah, 2002). in the construction industry the problem of defect normally happen in the building. In this study require greater care to identify the nature, causes and remedies defect. Studies conducted on the two systems at the residential area. There are many defects in buildings in Malaysia. Defects in buildings can be seen in both the IBS and conventional systems. Differences in building defects can be seen with in the various forms by the used of system. So far, the thesis to study the comparison of defects between conventional and IBS at residential buildings and how to control and solve the defect at the both system.